TELE-REHABILITATION SYSTEM AS AN APPLICATION OF MPEG-2 SYSTEM - Santoso, Petrus (Jurnal Teknik Elektro, 2003)
A Distributed Tele-Rehabilitation System is an application that helps remotely located clinicians work in a process of patient rehabilitation. With this system, clinicians are able to share medical information through the network to make diagnoses and discuss medical treatment for a patient. To enable the mentioned functionalities, the system uses MPEG-2 as an infrastructure. There are two kind of medical data that need special place in MPEG-2, Medical Rehabilitation Signal and Patient Medical Record. As a result of study literature and analysis process the following decision can be taken. Medical Rehabilitation Signal should be incorporated into PES Packet Data with elementary stream ID 0xBD. Patient Medical Record should be placed as descriptors in Program Map Table. Further on PDU format for Medical Rehabilitation Signal and Patient Medical Record has been decided. A prototype implementation shows that the Tele-Rehabilitation system can works well using MPEG-2 as an infrastructure. Abstract in Bahasa Indonesia : SSistem Tele-Rehabilitasi Terdistribusi adalah sebuah aplikasi yang membantu tenaga medis untuk melakukan proses rehabilitasi terhadap pasien. Dengan sistem ini, tenaga medis bisa melakukan diskusi jarak jauh dengan tenaga medis lain untuk memberikan perawatan yang paling tepat terhadap pasien. Untuk itu, MPEG-2 dipakai sebagai infrastruktur. Ada dua jenis data medis yang memerlukan tempat khusus dalam MPEG-2, Sinyal Rehabilitasi Medis dan Catatan Medis Pasien. Sebagai hasil dari literatur studi dan proses analisa, keputusan berikut telah diambil. Sinyal Rehabilitasi Medis seharusnya ditempatkan dalam Paket Data PES dengan stream elementer yang mempunyai ID 0xBD. Catatan Medis Pasien seharusnya ditempatkan sebagai descriptor dalam Program Map Table. Lebih jauh, format PDU untuk Sinyal Rehabilitasi medis dan Catatan Medis Pasien juga sudah ditentukan. Sebuah prototipe sudah diimpelementasikan dan menunjukkan bahwa Sistem Tele-Rehabilitasi dapat bekerja dengan baik menggunakan MPEG-2 sebagai infrastruktur. Kata kunci : MPEG-2, Distribusi Tele-Rehabilitasi Sistem.